Exploring the factors affecting global manufacturing performance*. Issue 1 (2nd January 2019) - Yeo, Benjamin; Grant, Delvin
ABSTRACT: A decision tree is used to explore the effects of Information and Communication Technologies (ICTs) and financial factors on global manufacturing industry sales performance. Existing research provides an unclear picture of how ICTs affect sales performance. Earlier studies showed little evidence that ICTs improve performance, more recent studies do. Our investigation found that between 2006 and 2009, companies with high ICT scores performed well, but their performance declined substantially between 2010 and 2014. ICTs do not significantly influence manufacturing sales growth performance, but financial factors do. Supplier credit as a source of financing leads to negative sales growth, while low loan collateral improves sales performance. Taking advantage of bank financing improves sales, but using equity or stocks to fund investments negatively affects them. These findings are used to develop seven research hypotheses for future studies.